A Gamble for God : St. Camillus de Lellis - Mayer, Maxine; Daughters of St. Paul. (Boston, MA : St. Paul Editions, 1983)
A biography of the Italian priest and saint who was the founder of the Ministers of the Sick, an order of priests devoted to hospital service, and is now revered as a patron of the sick.
Keywords: Camillus, -- de Lellis, Saint, -- 1550-1614 -- Juvenile literature; Camillus, -- de Lellis, Saint, -- 1550-1614.; Christian saints -- Italy -- Biography -- Juvenile literature; Saints; Hospitals -- History